EVALUATION OF THRUST FORCE IN DRILLING OF BD-CFRP COMPOSITE USING TAGUCHI ANALYSIS, RESPONSE SURFACE METHODOLOGY AND NEURAL NETWORK - Nagaraja; Herbert, Mervin A.; Shetty, Divakara; G S, Vijay; Shetty, Raviraj (European Scientific Journal, ESJ, 2013)
Drilling is the most frequently used machining operation in carbon fiber reinforced polymer (CFRP) composite materials. The quality of the drilled holes is significantly affected by the thrust force generated during drilling of CFRP composite materials. In the present work, an attempt has been made to study the effects of process parameters such as feed rate, spindle speed, drill diameter and point angle on thrust force in drilling of bi-directional carbon fiber reinforced polymer (BD-CFRP) composite laminate using Taguchi design of experiments (DOE), the response surface methodology (RSM) and the genetic algorithm optimized radial basis function neural network (GA-RBFNN). The analysis of variance (ANOVA) is also performed for investigating the influence of process parameters on machining process using high speed steel (HSS) drills. The results reveal that the drill diameter is the most significant design factor influencing the thrust force followed by the spindle speed. It is evident from the investigation that the experimental results of the thrust force in drilling of BD-CFRP composite laminate are in good agreement with the predicted results as per RSM and GA-RBFNN.